Factors Affecting Performance and Growth of Food Sector BUMD Jakarta Province - Siahaan, Henry MP; Priyarsono, Dominicus Savio; Rifin, Amzul; Arifin, Bustanul (UI Scholars Hub, 2021)
Through a quantitative approach to data analysis using SEM-PLS, this research aims to identify factors that can improve the performance and growth of the food sector BUMD of DKI Jakarta Province. This research was motivated based on the fact that most BUMDs in Indonesia underperform with various causes. Total respondents were 98 employees from middle to top level management positions in three food BUMDs in DKI Jakarta. The main findings of this research are 12 indicators (inner model) which are divided into five variables in the measurement model (outer model): management, organization, human resources, finance and technology that have a significant relationship and positive effect on all variables. While of the five variables used in the structural model, only financial variable has a significant effect on the performance of BUMD businesses. While the variables of performance improvement of management, organization, human resources and technology do not significantly improve the performance of BUMD businesses. Going forward, companies and the DKI Jakarta Provincial Government can focus on evaluating and improving the growth capital structure and business volume. The company's increased profitability will provide a multiplier effect on increasing the performance and growth of BUMD businesses.